The Role of MUI Fatwa as A Product of Islamic Law In Society - Madani, Mohammad Thoyyib; Rufaida, Rifki (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This article explores the role of Fatwa issued by the Indonesian Council of Ulama (MUI) as a product of Islamic law within society. As a central institution for religious authority in Indonesia, MUI plays a pivotal role in shaping and interpreting Islamic legal principles. The study delves into the impact and significance of MUI fatwas in influencing legal practices and social dynamics. By analyzing the development and implementation of MUI fatwas, the article aims to provide insights into their implications on Islamic law, community behavior, and the broader legal landscape. The research employs a multifaceted approach, combining legal analysis and sociocultural perspectives to comprehensively examine the multifaceted influence of MUI fatwas on Islamic legal practices within the Indonesian society. This study contributes to a deeper understanding of the dynamic interplay between Islamic legal pronouncements and their societal ramifications, shedding light on the intricate relationship between religious authority and legal norms in the contemporary context.